Translating Subtitles of Becoming Jane Film: A Pragmatic Approach - Arbain Arbain (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
Subtitling is an effective way to provide dialogues or narrative for a movie. The benefit is for people to enjoy the film even though its different from their native language. They enjoy movies over the world with different countries and styles by the dialogues translated. This research aims to know the strategy of responding to arguing in the file's subtitle titled Becoming Jane, to find out the translation techniques used by the translator, and to assess the translation quality in terms of the accuracy, acceptability, and readability. The research method is descriptive qualitative method with